Penerapan E-Government Pada Aplikasi Tangerang Live Dalam Meningkatkan Kualitas Informasi Publik di Kota Tangerang - Muhammad Adam Kusuma; Abdul Rahman (Eksekusi : Jurnal Ilmu Hukum dan Administrasi Negara, 2025)
This study aims to analyze the implementation of e-government within the Tangerang LIVE application, an integrated digital platform that consolidates various public service applications of the Tangerang City Government. Although the application is designed to streamline access to public services, challenges remain—particularly in the area of slow information management, which affects service efficiency. The analysis is based on four key e-government indicators: Efficiency, Trust, Reliability, and Citizen Support. Findings reveal that, in terms of efficiency, the application features a user-friendly interface that enhances accessibility, though some technical issues still hinder optimal use. Regarding trust, the application has generally earned positive public perception, though constructive feedback highlights areas for enhancement. From the reliability perspective, despite ongoing performance monitoring, the application has not consistently met expectations in terms of stable and dependable service delivery. Lastly, the citizen support aspect has shown progress through the availability of a helpdesk system; however, improvements are needed in responsiveness and overall effectiveness to better serve users. These findings suggest that while Tangerang LIVE reflects several aspects of successful e-government implementation, continuous improvements—particularly in system performance, responsiveness, and two-way communication—are essential to enhance public information quality and user satisfaction. Strengthening these areas is key to achieving a more transparent, efficient, and citizen-oriented digital government platform.